Structural analysis of the Trypanosoma brucei EIF4E6/EIF4G5 complex reveals details of the interaction between unusual eIF4F subunits - Penteado, Renato Ferras (2024)
Supplementary Information The online version contains supplementary material available at https://doi.org/10.1038/s41598-024-52364-1.